At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

Please explain I don’t I understand help

Please Explain I Dont I Understand Help class=

Sagot :

Answer:

Step-by-step explanation:

f (x) = (5(-4)) + a) (3/5 + 4) ( 6 + b)

f (x) = (-20 + a) (6 2/5) (6 + b)

f ( -20 ) = -20 + -20 (a) (6 2/5) (6 + b)

f ( -20 - 6 2/5 ) = (a) (6 2/5 -6 2/5) (6 + b)

f (-26 2/5 - 6 ) = (a) (6-6 +b)

f (-32 2/5-6) = (a) (b)